Characterizing CD38 Expression and Enzymatic Activity in the Brain of Spontaneously Hypertensive Stroke-Prone Rats - Hannawi, Yousef; Ewees, Mohamed G.; Moore, Jordan T.; Zweier, Jay L. (Frontiers in Pharmacology, 2022)
Background: CD38 is a transmembrane glycoprotein that catabolizes nicotinamide adenine dinucleotide (NAD+) and is the main source for the age-dependent decrease in NAD+ levels. Increased CD38 enzymatic activity has been implicated in several neurological diseases. However, its role in the pathogenesis of cerebral small vessel disease (CSVD) remains unknown. We aimed to characterize CD38 expression and enzymatic activity in the brain of spontaneously hypertensive stroke-prone rats (SHRSP), a genetic model for hypertension and human CSVD, in comparison to age-matched normotensive Wistar Kyoto rats (WKY). Materials and Methods: Age-matched male 7- and 24-week-old WKY and SHRSP were studied. CD38 enzymatic activity was determined in the brain homogenate. Immunohistochemistry and Western Blotting (WB) were used to characterize CD38 expression and localize it in the different cells within the brain. In addition, expression of nitric oxide synthase (NOS) isoforms and the levels of nitric oxide (NO), superoxide, nicotinamide dinucleotide phosphate NAD(P)H were measured in WKY and SHRSP. Results: CD38 expression and enzymatic activity were increased in SHRSP brains compared to age matched WKY starting at 7 weeks of age. CD38 expression was localized to the endothelial cells, astrocytes, and microglia. We also identified increased CD38 expression using WB with age in SHRSP and WKY. CD38 enzymatic activity was also increased in 24-week SHRSP compared to 7-week SHRSP. In association, we identified evidence of oxidative stress, reduced NO level, reduced NAD(P)H level and endothelial NOS expression in SHRSP compared to age matched WKY. NAD(P)H also decreased with age in WKY and SHRSP. Additionally, activation of astrocytes and microglia were present in SHRSP compared to WKY. Conclusions: CD38 is overexpressed, and its enzymatic activity is increased in SHRSP, a genetic model for marked hypertension and human CSVD. Our results suggest a potential role for CD38 enzymatic activation in the pathogenesis of CSVD that needs to be confirmed in future mechanistic studies.